Machine Learning Quick Reference Quick and Essential Machine Learning Hacks for Training Smart Data Models. - Kumar, Rahul (Packt Publishing Ltd, 2019)
Machine learning involves development and training of models used to predict future outcomes. This book is a practical guide to all the tips and tricks related to machine learning. It includes hands-on, easy to access techniques on topics like model selection, performance tuning, training neural networks, time series analysis and a lot more.